Nota sobre Lernaeenicus longiventris Wilson e sua ocorrência em Xenomelaniris brasiliensis (Quoy & Gaimard): (Crustacea, Copepoda - pisces, Atherinidae) (Boletim do Instituto Oceanográfico, 1953)
This note records the occurrence of a parasitic copepod Lernaeenicus longiventris Wilson, found on Xenomelaniris brasiliensis (Quoy & Gaimard). 285 specimens of Atherinidae caught at Cananeia in the waters in front of the Research Base of this Institute were used in this investigation. In this material the author found 79 infested specimens (23 ;and 56 ;) which amounts to 27,7% of the total. After making a reference to the presence of epizoic organisms that were only found on the samples of December 1952 and January 1953 the author shows the parasit distribution on each sex being evident that the female specimens were more subject to parasitism. In the opinion of the authors majority the individuals of the genus Lernaeenicus penetrate in the host flesh in search of vasculated zones in order to obtain a blood supply as food. Although in some cases it seems that this tendency actually exists, the writer was able to find in the major part of his observations that the parasit had followed an absolutely superficial path which is a fact that invalidates totally the hypothesis that the parasits are properly hematophagous but instead it shows that they feed almost exclusively on their hosts tissues lymph. Three cases of fixation of the parasit in the ocular zone are recorded by the author snowing that the larvae not always penetrates in the conjunctival dermal layer. The eyes parasits have not been found structurally different from the other specimens found on other parts of the body as it has been stated by some authors.